2023
DOI: 10.7150/thno.86930
|View full text |Cite
|
Sign up to set email alerts
|

Applications of injectable hemostatic materials in wound healing: principles, strategies, performance requirements, and future perspectives

Hong Wang,
Liang Yang

Abstract: Uncontrolled traumatic bleeding can lead to death due to excessive blood loss within minutes. Early intervention is crucial to save lives, making timely and effective hemostasis is a major global challenge. Injectable hemostatic materials (IHMs) have been proposed to improve the effectiveness of hemostasis, facilitate wound healing, and enhance survival rates in emergency situations. The superior hemostatic performance of IHMs has garnered significant attention. However, there are relatively few comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 144 publications
0
6
0
Order By: Relevance
“…This difference between F2 and F3 displays that TA has a fast-release profile and performs its role in hemostasis. Electrospun nanofibers are widely recognized as excellent candidates for hemostatic applications due to their distinctive properties, including high porosity, small diameter, and large surface area [95][96][97]. This investigation has revealed that the incorporation of drugs and the strategic manipulation of their distribution within the nanofibers can significantly enhance their hemostatic capabilities.…”
Section: In Vitro Hemostatic Time Testmentioning
confidence: 99%
“…This difference between F2 and F3 displays that TA has a fast-release profile and performs its role in hemostasis. Electrospun nanofibers are widely recognized as excellent candidates for hemostatic applications due to their distinctive properties, including high porosity, small diameter, and large surface area [95][96][97]. This investigation has revealed that the incorporation of drugs and the strategic manipulation of their distribution within the nanofibers can significantly enhance their hemostatic capabilities.…”
Section: In Vitro Hemostatic Time Testmentioning
confidence: 99%
“…This structure undergoes a coagulation cascade with a coagulation factor exudate to stop the bleeding and temporarily protect the injured area. 24,25 Subsequently, inflammatory cells, including macrophages and neutrophils, converge at the wound location to clear foreign bodies, damaged endogenous tissues, apoptotic cells, and bacterial proteases. Meanwhile, other immune cells are attracted to the wound site via the release of reactive oxygen species (ROS), chemokines, vasoactive factors, and other mediators to aid in tissue restoration.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29] The research and development of IHMs have become a current hotspot and challenge. 30 Currently, the research related to IHMs provides good inspiration for the treatment of uncontrollable traumatic bleeding. To comprehensively elaborate the development trend and research status of IHMs, this paper provides a comprehensive visual summary of the research on IHMs (shown in Figure 2), and focuses on the mapping relationship of the research on IHMs based on the visualization technology, and finally looks forward to the future development direction, which will provide guidance for the development of the hemostatic materials and their clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Injectable hemostatic materials (IHMs), as a new type of hemostatic material, have the advantages of good hemostatic effect, antimicrobial properties, and biodegradability, which have attracted widespread attention and interest 20–29 . The research and development of IHMs have become a current hotspot and challenge 30 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation